Association of Histologic Parameters with Outcome in C3 Glomerulopathy and Idiopathic Immunoglobulin-Associated Membranoproliferative Glomerulonephritis. Issue 7 (July 2022) - Lomax-Browne, Hannah J.; Medjeral-Thomas, Nicholas R.; Barbour, Sean J.; Gisby, Jack; Han, Heedeok; Bomback, Andrew S.; Fervenza, Fernando C.; Cairns, Thomas H.; Szydlo, Richard; Tan, Sven-Jean; Marks, Stephen D.; Waters, Aoife M.; et al.
Visual Abstract: Abstract : Background and objectives: C3 glomerulopathy and idiopathic Ig-associated membranoproliferative GN are kidney diseases characterized by abnormal glomerular complement C3 deposition. These conditions are heterogeneous in outcome, but approximately 50% of patients develop kidney failure within 10 years. Design, setting, participants, & measurements: To improve identification of patients with poor prognosis, we performed a detailed analysis of percutaneous kidney biopsies in a large cohort of patients. Using a validated histologic scoring system, we analyzed 156 native diagnostic kidney biopsies from a retrospective cohort of 123 patients with C3 glomerulopathy and 33 patients with Ig-associated membranoproliferative GN. We used linear regression, survival analysis, and Cox proportional hazards models to assess the relationship between histologic and clinical parameters with outcome. Results: Frequent biopsy features were mesangial expansion and hypercellularity, glomerular basement membrane double contours, and endocapillary hypercellularity. Multivariable analysis showed negative associations between eGFR and crescents, interstitial inflammation, and interstitial fibrosis/tubular atrophy. Proteinuria positively associated with endocapillary hypercellularity and glomerular basement membrane double contours. Analysis of second native biopsies did not demonstrate associations between immunosuppression treatment and improvement in histology. Using a composite outcome, risk of progression to kidney failure associated with eGFR and proteinuria at the time of biopsy, cellular/fibrocellular crescents, segmental sclerosis, and interstitial fibrosis/tubular atrophy scores. Conclusions: Our detailed assessment of kidney biopsy data indicated that cellular/fibrocellular crescents and interstitial fibrosis/tubular atrophy scores were significant determinants of deterioration in kidney function.